Análise dos preços de OPME utilizados em procedimentos cirúrgicos do trato gastrointestinal no SUS - Pasquali, Elisa (My University, 2025)
The Brazilian Unified Health System (SUS) is the largest public health system in the world, founded on the principles of universality, equity, and comprehensiveness. The SIGTAP system standardizes and reimburses procedures, including the use of Orthoses, Prostheses, and Special Materials (OPME), which are essential in surgeries, although the reimbursement often does not cover their actual cost. Thus, the objective of this study was to analyze and compare the prices of OPME used in gastrointestinal surgical procedures with the reimbursement values established by SIGTAP. The data collected refers to the period of the year 2024 from the governmental platforms Painel de Preços, SIGTAP, and SIH/SUS. Gastrointestinal procedures with expected use of OPME were identified, and their acquisition costs were compared with the amounts established in SIGTAP, also correlating CATMAT and SIGTAP codes. The discussion highlighted discrepancies between reimbursements and average public acquisition prices, indicating that the transferred amount does not represent the total hospital cost. Variations between items and limitations in the standardization between SIGTAP and CATMAT were also observed, as well as specific differences in the materials analyzed. [resumo fornecido pelo autor]
O SUS é o maior sistema público de saúde do mundo, fundamentado nos princípios de universalidade, equidade e integralidade. O sistema SIGTAP padroniza e remunera procedimentos, incluindo o uso de Órteses, Próteses e Materiais Especiais (OPME), essenciais em cirurgias, embora muitas vezes o repasse não cubra seu custo real. Assim, o objetivo deste estudo foi analisar e comparar os preços de OPME utilizados em procedimentos cirúrgicos do trato gastrointestinal com os valores repassados pelo SIGTAP. Os dados coletados são referentes ao período do ano de 2024, nas plataformas Painel de Preços, SIGTAP e SIH/SUS. Foram identificados os procedimentos gastrointestinais com previsão de uso de OPME e comparados seus custos de aquisição com os valores previstos no SIGTAP, correlacionando também códigos CATMAT e SIGTAP. A discussão evidenciou discrepâncias entre repasses e preços médios de aquisição pública, indicando que o valor transferido não representa o custo hospitalar total. Observou-se ainda variação entre itens e limitações na padronização entre SIGTAP e CATMAT, além de diferenças específicas nos materiais analisados. [resumo fornecido pelo autor]
Keywords: Sistema Único de Saúde (Brasil); Hospitais - Custo operacional; Financiamento governamental; Grampeadores cirúrgicos